The Influence of Self-Efficacy in Mediated Individual Characteristics on Leadership Learning Performance in PT X - Tasnim RahmatTasnim Rahmat (Jurnal Educative: Journal of Educational Studies, 2021)
The achievement of learning performance can create benefits for a company both in increasing employee competence and company productivity. The cost spent, however, is usually not proportional to the graduation rate and returns on the company. Self-efficacy is a performance predictor. Individual characteristics have a strong role in the effectiveness of learning. This research aims to test the role of individual characteristics in  leadership learning performance with self-efficacy as a mediator variable. The data in this study are secondary data owned by PT X. This data were processed by parallel mediation analysis model using Macro PROCESS and SPSS software. The results showed that self-efficacy is able to mediate the role of individual characteristics in leadership learning performance. This research found that self-efficacy and continuous learning ability were able to partially mediate the role of individual characteristics in leadership learning performance. Thus, by adding indirect effect of mediator variable, it can further enhance the role of individual characteristics in leadership learning performance.Tercapainya kinerja pembelajaran dapat memberikan manfaat bagi perusahaan baik dalam peningkatan kompetensi karyawan maupun produktivitas perusahaan. Biaya yang dikeluarkan, bagaimanapun, biasanya tidak sebanding dengan tingkat kelulusan dan pengembalian perusahaan. Self-efficacy adalah prediktor kinerja. Karakteristik individu memiliki peran yang kuat dalam efektivitas pembelajaran. Penelitian ini bertujuan untuk menguji peran karakteristik individu dalam kinerja pembelajaran kepemimpinan dengan efikasi diri sebagai variabel mediator. Data dalam penelitian ini adalah data sekunder milik PT X. Data ini diolah dengan model analisis mediasi paralel menggunakan software Macro PROCESS dan SPSS. Hasil penelitian menunjukkan bahwa efikasi diri mampu memediasi peran karakteristik individu dalam kinerja pembelajaran kepemimpinan. Penelitian ini menemukan bahwa efikasi diri dan kemampuan belajar berkelanjutan secara parsial mampu memediasi peran karakteristik individu dalam kinerja pembelajaran kepemimpinan. Dengan demikian, dengan menambahkan pengaruh tidak langsung dari variabel mediator dapat lebih meningkatkan peran karakteristik individu dalam kinerja pembelajaran kepemimpinan.